ANALISIS PENGARUH GROWTH OPPORTUNITY, NET WORKING CAPITAL, DAN CASH CONVERSION CYCLE TERHADAP CASH HOLDINGS PERUSAHAAN SEKTOR PERTAMBANGAN - William William; Syarief Fauzi (Ekonomi dan Keuangan, 2013)
This Research investigates factors that influence the Cash Holdings level of public listed mining companies. The main aim of this research is to analyze the relationships between Growth Opportunity, Net Working Capital, and Cash Conversion Cycle with Cash Holdings of public listed mining companies. The data used in this research is the data of 18 public listed mining companies in which collected through purposive sampling method by criterions (1) Company with positive equity within 2009-2011 (2) Company with total assets growth below or equal to 100% in period 2008-2011 (3) Company with cash/total assets rasio greater than zero and below than 1 (0 < cash/total assets < 1) in 2009-2011. This research employs panel data regression model due to the data in this research share the characteristic of panel data and fixed effect model (FEM) is believed to be appropriate model because the value of intercept in this research is individually different. With Eviews 7, before conducting the goodness of fit tests, the normality test and redundant fixed effect test is conducted firstly to identify whether the data is normally distributed and to determine the appropriateness of fixed effect model in this research. Finally, the estimation process is conducted to present the results of this research. This study shows that Growth Opportunity, Net Working Capital, and Cash Conversion Cycle simultaneously and partially have significant impact towards Cash Holdings with 95% of confidence level. Furthermore the R-squared coefficient shows that Growth Opportunity, Net Working Capital, and Cash Conversion Cycle can give 88,89%  explanation to Cash Holdings. Keywords:  Growth Opportunity, Net Working Capital, Cash Conversion Cycle, Cash Holdings